Systematic Mapping of Corporate Social Responsibility Topics for 2015-2021 Based on Bibliometric Analysis (Universitas Muhammadiyah Yogyakarta, 2024)
Research aims: This study used bibliometric analysis to produce a comprehensive mapping of corporate social responsibility (CSR) research. This study examined changes in citations, publication trends, author collaboration, trend title, trend author keywords, trend abstract, nations, dominating factors, research development, and future research in corporate social responsibilities papers from the Scopus index with a range of 2015-2021. Design/Methodology/Approach: This research employed bibliometric analysis methods. The research sample used was 1,567 articles with the keyword